2017
DOI: 10.1589/jpts.29.622
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of ankle balance taping on dynamic and static balance of soccer players with acute ankle sprain

Abstract: [Purpose] This study aimed to evaluate the immediate effect of ankle balance taping on balance ability of soccer players with acute ankle sprain. [Subjects and Methods] This study was conducted with 16 subjects who were diagnosed with ankle sprain. A cross-over randomized design was used. Each subject performed three interventions in a random order. Subjects were randomly assigned to an ankle balance taping, placebo taping, and no taping. For dynamic and static balance, ability was measured using BIORescue (RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…Forty-five studies investigating the effect of Kinesio taping on balance of four different populations were included and the tools/analyses used were the star excursion balance test, 26 41 center of pressure behavior (force plate), 32,42 52 stabilometer devices 53 62 or errors during postural control (flamingo test, ballet movements, hop test, Balance Error Scoring System and single-legged stance). 26,39 41,51,63 69 Meta-analyses were carried out for healthy and older people, and people with chronic ankle instability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-five studies investigating the effect of Kinesio taping on balance of four different populations were included and the tools/analyses used were the star excursion balance test, 26 41 center of pressure behavior (force plate), 32,42 52 stabilometer devices 53 62 or errors during postural control (flamingo test, ballet movements, hop test, Balance Error Scoring System and single-legged stance). 26,39 41,51,63 69 Meta-analyses were carried out for healthy and older people, and people with chronic ankle instability.…”
Section: Resultsmentioning
confidence: 99%
“…- People after Ankle Sprain : Two low-quality studies 38,49 compared Kinesio taping to no tape and sham, and both studies reported small balance improvement for the Kinesio taping group in contrast to the comparison group (Supplementary Material 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have reported the benefits of balance with the use of other ankle bandages, such as kinesiology tape in healthy individuals and athletes. 47 , 48 This disparity in results could be explained by the fact that different material properties affect the somatosensory outcomes or provide greater elasticity range. 48 In this context, disturbances in motor control, poor balance, or lack of neuromuscular aptitudes have been described as predictors of risk of injury in the lower limb.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 This disparity in results could be explained by the fact that different material properties affect the somatosensory outcomes or provide greater elasticity range. 48 In this context, disturbances in motor control, poor balance, or lack of neuromuscular aptitudes have been described as predictors of risk of injury in the lower limb. Consequently, all these aspects must be edconsideration before implementation of bracing or AT approaches in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Meskipun basket dapat dibandingkan dengan sepak bola dalam beberapa aspek, ada beberapa perbedaan berdasarkan kinerja yang mungkin menjelaskan perbedaan dalam hasil studi. Pada jurnal ke empat yang berjudul "Immediate effect of ankle balance taping on dynamic and static balance of soccer players with acute ankle sprain" yang ditulis oleh (Shin and Kim, 2017) yang hasilnya adalah Limits of stability (LOS) ukuran keseimbangan dinamis meningkat secara signifikan dibandingan dengan placebo taping dan tidak menggunakan taping. Penerapan Ankle Balance Taping yang menggunakan kinesiology tape secara instan meningkatkan kemampuan keseimbangan statis dan dinamis pemain sepak bola dengan ankle sprain.…”
Section: Pembahasanunclassified